Conceptualizing forgiveness: a review and path forward - Brady, Daniel L. (2022)
Forgiveness is a valuable conflict management strategy that has numerous benefits in workplace settings (e.g., for employees, team dynamics, dyadic relationships, and organizations). However, important conceptual questions have emerged, especially as scholars have begun to examine forgiveness in the workplace. To better understand these issues, we conduct a critical review and analysis of the extant literature to identify key conceptual issues that are creating challenges for the study of forgiveness in organizational behavior. Building on these insights, we propose that conceptualizing forgiveness as a special case of emotion regulation can provide a strong conceptual and theoretical foundation that can address these challenges. Moreover, we outline how this approach can create exciting new research avenues that can enhance our theoretical understanding of forgiveness (e.g., distinguishing between the processes underlying forgiveness; identifying points of intervention to promote forgiveness; exploring the role of time in forgiveness; examining how context impacts forgiveness). We also identify how this approach can provide novel practical insights into how forgiveness can be facilitated and effectively managed in the workplace.